2016
DOI: 10.1097/hcr.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Various Exercise Tests for Assessing the Response to Pulmonary Rehabilitation in Patients With COPD

Abstract: On the basis of these data, all exercise measures were responsive to PR. Indices derived from cycling in the laboratory appeared more responsive than indices derived from walking in the field when assessed by effect size, but this finding and its possible clinical significance requires confirmation in a larger study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Assessment of exercise tolerance at the start of PR is also necessary to formulate the exercise prescription. Several methods of exercise assessment are validated for use in PR, and are responsive to the PR intervention . CPET evaluates the integrated cardiovascular, ventilatory and musculoskeletal response to exercise.…”
Section: Patient Assessment and Outcomes Measurement In Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of exercise tolerance at the start of PR is also necessary to formulate the exercise prescription. Several methods of exercise assessment are validated for use in PR, and are responsive to the PR intervention . CPET evaluates the integrated cardiovascular, ventilatory and musculoskeletal response to exercise.…”
Section: Patient Assessment and Outcomes Measurement In Prmentioning
confidence: 99%
“…Repeat (second) walk tests improve validity and precision of test performance, hence second walks should be performed when used in PR programmes . Changes in exercise capacity following PR do not necessarily correlate with changes in QOL, and changes in one exercise test do not always correlate with improvements in others …”
Section: Patient Assessment and Outcomes Measurement In Prmentioning
confidence: 99%
“…The 6MWT is reported as a valid and reliable field test and reflects performance of more activities of daily life [ 4 ]. A previous study found that changes in dyspnea grade, patient-reported outcomes, 6-min walk distance (6MWD), and cycle endurance time (constant work-rate test), after pulmonary rehabilitation, did not show synchronous responses in patients with COPD, suggesting the need for various tests to evaluate the response in exercise intolerance [ 29 ]. Therefore, we proposed that 6MWT, ISWT, and CPET be used complementary to each other to evaluate the exercise capacity of patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Field tests are routinely used to evaluate the functional benefits following a PR program in patients with chronic lung disease,10 such as the 6-minute walk test (6MWT)1114 or the incremental shuttle walking test 15. In clinical practice, the 6-minute stepper test (6MST) has been recently proposed as a convenient method to evaluate exercise tolerance because the test can be easily implemented, is inexpensive and feasible to be performed at medical offices or patients’ homes 1619.…”
Section: Introductionmentioning
confidence: 99%